Analysis of the Influence of Macro Fundamentals, Company Growth, Capital Structure on Stock Returns with Dividend Policy, Financial Performance in Consumer Non-Cyclicals Sector Companies Listed on the Indonesia Stock Exchange in 2021-2024 - Linda Afifah; Hwihanus (Tinta Emas Institute, 2025)
This study aims to analyze the impact of macroeconomic fundamentals, company growth, and capital structure on stock returns, considering dividend policies and financial performance, with a focus on the consumer non-cyclicals sector listed on the Indonesia Stock Exchange from 2021 to 2024. Using quantitative methods, the research employs data from five consumer non-cyclicals companies, analyzed through Smart PLS 4 software. The findings reveal that macroeconomic fundamentals, such as inflation, GDP, and exchange rates, significantly affect stock returns but do not significantly influence dividend policies or financial performance. Company growth, measured by total asset turnover, has a significant negative effect on dividend policies, while it positively influences financial performance, especially Return on Assets (ROA) and Return on Equity (ROE), and negatively affects stock returns. The capital structure, represented by the Debt to Equity Ratio (DER), does not show a significant impact on dividend policies, financial performance, or stock returns. Additionally, financial performance, particularly ROA and ROE, has a significant positive effect on stock returns. This research provides valuable insights for investors and company management in making informed decisions within the consumer non-cyclicals sector. Future studies could explore other sectors and extend the research period for broader applicability.